The Principal's Strategy in Improving the Quality of Teacher Performance in the Learning Process in Islamic Elementary Schools - Alwi, Musdalifah; Mumtahana, Lusia; Alai, Ashimatul; Azzukhrufi, Jaya Roza; Romadhan, Moh. Syahru (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
The research objectives in this writing are (1) How is the teacher's performance in the learning process during a pandemic in shaping the noble character of students? (2) What is the principal's strategy in improving the quality of teacher performance in the learning process without leaving the educational institution's mission, namely to form the noble character of students? (3) What are the inhibiting and supporting factors experienced by school principals in improving the quality of teacher performance in the learning process by forming students' noble character? The research method used by researchers is a qualitative method using data collection techniques through interviews, observation, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions to test the validity of the data using extended attendance, observation, triangulation of sources and methods, and discussions with colleagues. From the results of this study, the researchers concluded that: (1) the quality of the performance of local teachers has decreased due to the pandemic which limited the space for interaction to carry out teaching and learning activities. (2) The principal's strategy is very influential and needed in improving teacher performance in the learning process. (3) there are several inhibiting factors in implementing the principal's strategy.